Por trás de toda fuga, nem sempre há um crime: o Recrutamento a laço e os limites da ordem no Ceará (1850-1875) - Ramos, Xisley Araújo (2003)
This dissertation - "Behind any escape, there is not even a crime": The recruitment by force and the order limits in Ceara (1850-1875), has an aim toanalyze the process of military recruitment by force for the potions of the army and the National Guard, in the second mid of the 1800's located in Ceara backlands - as a control strategy and regulation of the free and poor levels of the society - and fair position of the authorities that involved poor people, landlords and the Government. To present my reflections about the subject here proposed, this work was divided in three chapters. In the first one, I discuss, based on history and archive documents, the condition of the free and poor man in Ceara and the severaI types of negotiation between rural workers and the local landlords. In the second chapter, I analyze the recruitment by force in the election process and the political offices. I also point out the military institutions and the brazilian soldier social value in the proposed period as well as the patriot speech that I had tried to spread ali over the society levels, becoming true in actions that could take the poor man to the voluntary and the struggle for his homeland. In the last chapter, I analyze the local and imperial govemment difficulties in attracting soldiers to the War of Paraguay, leaving the local society against the process of recruitment by force and a certain affliction in the order of the social relations Iived among the poor men, landlords and the Government.